Historical Earnings, Accrual Accounting, and Future Cash Flows: A Malaysian Perspective - Ali, Mazurina Mohd; Ali, Kamalia Mohamed; Bashatweh, Ammar Daher; Hasnan, Suhaily (The Economics and Finance Letters, 2022)
This study investigates the influence of historical earnings and historical accrual accounting on projecting future cash flows. The sample consisted of 159 construction, energy, and property development companies from the main capital market of Malaysia. The compiled data of these companies spanned from 2015 to 2019 and was collected from the financial statements of the companies, including operating cash flows and earnings. The profit or loss statement and cash flow statement were used for calculating historic accrual accounting. Earnings, cash flow, and accrual accounting models were used as the basis for the regression model construction. The accounting data demonstrated that the prediction performance of the models was improved by the three-year lag. The previous two-year earnings and accrual accounting had positive and significant predictive power for forecasting future cash flows. Moreover, the past one- and two-year cash flows from operations significantly predicted future cash flows. These results are important for a sound understanding among academics and practitioners of the crux of historical earnings, operating cash flow, and accrual accounting. The findings can assist corporate leaders and management executives in tracking the sustainability and financial growth of an organization.